Synonymous Mutations of Porcine Igf1r Extracellular Domain Affect Differentiation and Mineralization in MC3T3-E1 Cells - Wang, Chunli; Wang, Siyao; Liu, Songcai; Cheng, Yunyun; Geng, Hongwei; Yang, Rui; Feng, Tianqi; Lu, Guanhong; Sun, Xiaotong; Song, Jie; Hao, Linlin (Frontiers in Cell and Developmental Biology, 2020)
Due to the wide application of miniature pigs in biomedicine, it is necessary to elucidate the formation mechanism of its short stature. The insulin-like growth factor 1 receptor (IGF-1R), which receives signals by its extracellular domain (ECD) binding with ligand, is crucial in regulating cell growth and bone matrix mineralization. In this study, two haplotypes of IGF-1R with four synonymous mutations in the coding sequences of IGF-1R ECD between large and miniature pigs, were stably expressed in the IGF-1R-Knockout MC3T3-E1 cells, respectively, named as MC3T3-LP cells (LP group) and MC3T3-BM cells (BM group). The BM group showed a lower expression of IGF-1R than LP group both in transcription and translation levels, and showed proliferation inhibition. In addition, the IGF-1R in BM group promoted early stage differentiation and delayed late stage differentiation, which not only suppressed expression of bonerelated factors but also reduced ALP activity and calcium deposition. Moreover, different haplotypes of IGF-1R changed the stability and conformation of the protein, further affected the binding with IGF-1. Our data indicated that the four synonymous mutations of IGF-1R ECD may affected transcription and translation of gene, different IGF-1R folding patterns and the interactions with the IGF-1 resulting in the differences of the differentiation and mineralization of osteoblasts.